Atmospheric particulate pollution in South American megacities - la Colla, Noelia Soledad (2021)
Air pollution is one of the major problems caused by urban growth, and both industrial and automobile emissions have been the main causes of air quality deterioration in cities since the beginning of the 20th century. Atmospheric pollution is the largest single environmental risk for health causing about 7 million human deaths per year. On a global scale, developing countries are major contributors to air pollution due to their rising economies, with rapid industrial and population growth combined with poor emission controls. In South America there are five megacities (Bogotá, Buenos Aires, Lima, Rio de Janeiro and São Paulo) with over 10 million people potentially contributing to wide-ranging environmental consequences.Atmospheric particulate matter (APM) plays a leading role in the transport of trace metals and metalloids through the atmosphere and are chemical markers of air quality. The presence of these pollutants in APM has a detrimental effect on both the air quality and human health. In this review we provide an integrated assessment of hazardous metals and metalloids in the fine and coarse APM fractions, focusing on the South American megacities. We identified the current state of research for Ba, Cd, Cr, Cu, Mo, Ni, Pb, Pd, Pt, Rh, Sb, Sn, V and Zn, and summarized the findings in the 21st century. The findings of this review highlighted that despite the phasing out of leaded gasoline, Pb continues to be a metal pollutant with one of the highest atmospheric emission rates, mainly due to vehicular pollution. The megacities from Brazil and Argentina were, by far, those with the highest number of studies performed. However, updated research is needed for the five megacities, including specific studies on fine and ultrafine particulate matter fractions as these pose serious human health issues. Urban agglomerations denoted sustained increases of most metals over time that is indicative of deteriorating air quality. Nickel and Cd concentrations in megacities from Argentina, Brazil and Colombia, as well as Pb in one study from Colombia, were found to have exceeded international air quality guidelines.